2010
DOI: 10.1016/j.jbiomech.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of idealized joint geometry on finite element predictions of cartilage contact stresses in the hip

Abstract: Computational models may have the ability to quantify the relationship between hip morphology, cartilage mechanics and osteoarthritis. Most models have assumed the hip joint to be a perfect ball and socket joint and have neglected deformation at the interface between bone/cartilage. The objective of this study was to analyze finite element (FE) models of hip cartilage mechanics with varying degrees of simplified geometry and a model with a rigid bone material assumption to elucidate the effects on predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(200 citation statements)
references
References 42 publications
15
181
4
Order By: Relevance
“…Using the subject-specific kinematics data, the femur was oriented with respect to the pelvis according to the squat interval. The X-Y-Z-axis corresponds with the left hip's lateral-posterior-superior directions neglected [1,2,9,38], the peak stresses in our FEA were not situated on the cartilage, but instead were located on the underlying bone of the acetabulum [37,43]. These peaks could have been due to the lower elastic modulus of the cartilage layer.…”
Section: Discussionmentioning
confidence: 92%
“…Using the subject-specific kinematics data, the femur was oriented with respect to the pelvis according to the squat interval. The X-Y-Z-axis corresponds with the left hip's lateral-posterior-superior directions neglected [1,2,9,38], the peak stresses in our FEA were not situated on the cartilage, but instead were located on the underlying bone of the acetabulum [37,43]. These peaks could have been due to the lower elastic modulus of the cartilage layer.…”
Section: Discussionmentioning
confidence: 92%
“…In general, the thicker cartilage revealed a larger area in contact, but also a higher peak pressure. Kim et al constructed a FE model of the pelvis of a 10-year old child and used an experimental study to adjust the material properties from an adult's to a child's [25]. Their updated bone material properties were in accordance with the findings by Currey and Butler [28].…”
Section: Validationmentioning
confidence: 73%
“…Unfortunately, they did not evaluate their model against a FE model with elastic bones despite Anderson et al demonstrated that assuming rigid bones might alter cartilage contact stresses in the hip joint [7]. Anderson et al investigated the impact of several common simplifications in FE models [25]. Using a model with subject-specific bone geometry, cartilage thickness, and bone material properties as the gold standard, they found models with constant cartilage thickness to overestimate contact cartilage pressure and underestimate contact area.…”
Section: Validationmentioning
confidence: 99%
“…In the computational model, bones keep their relations on the neutral position of the foot, the same as its situation at imaging time. Each bone was defined as a flexible body in the software (Anderson et al, 2010). In this study, quasi-physiologic loading parameters including periodic loading, as well as time-dependent and viscoelastic properties have not been considered (Anderson et al, 2007;Chegini et al, 2009).…”
Section: Computational Modelmentioning
confidence: 99%